The association between total bile acid and bone mineral density among patients with type 2 diabetes - Yang, Song; Li, Hongyun; Gu, Yuanyuan; Wang, Qiang; Dong, Li; Xu, Chao; Fan, Yuxin; Liu, Ming; Guan, Qingbo; Ma, Lixing (Frontiers in Endocrinology, 2023)
Objective Bile acids have underlying protective effects on bones structure. Long-term diabetes also causes skeletal disorders including osteoporosis, Charcot arthropathy and renal osteodystrophy. Nevertheless, few studies have reported whether bile acid is associated with bone metabolism in diabetics. This study aimed to explore the relationship between total bile acid (TBA) and bone mineral density (BMD) among patients with type 2 diabetes mellitus (T2DM). Methods We retrospectively included 1,701 T2DM patients who were hospitalized in Taian City Central Hospital (TCCH), Shandong Province, China between January 2017 to December 2019. The participants were classified into the osteopenia (n = 573), osteoporosis (n= 331) and control groups (n= 797) according to BMD in the lumbar spine and femoral. The clinical parameters, including TBA, bilirubin, vitamin D, calcium, phosphorus and alkaline phosphatase were compared between groups. Multiple linear regression was used to analyze the relationship between TBA and BMD in lumbar spine, femoral, trochiter, ward's triangle region. A logistic regression was conducted to develop a TBA-based diagnostic model for differentiating abnormal bone metabolism from those with normal BMD. We evaluated the performance of model using ROC curves. Results The TBA level was significantly higher in patients with osteoporosis (Median[M]= 3.300 μmol/L, interquartile range [IQR] = 1.725 to 5.250 μmol/L) compared to the osteopenia group (M = 3.200 μmol/L, IQR = 2.100 to 5.400 μmol/L) and control group (M = 2.750 μmol/L, IQR = 1.800 to 4.600 μmol/L) (P <0.05). Overall and subgroup analyses indicated that TBA was negatively associated with BMD after adjusted for the co-variates (i.e., age, gender, diabetes duration, BMI, total bilirubin, direct bilirubin, indirect bilirubin) (P <0.05). Logistic regression revealed that higher TBA level was associated with increased risk for abnormal bone metabolism (OR = 1.044, 95% CI = 1.005 to 1.083). A TBA-based diagnostic model was established to identify individuals with abnormal bone metabolism (T-score ≤ -1.0). The area under ROC curve (AUC) of 0.767 (95% CI = 0.730 to 0.804). Conclusion Our findings demonstrated the potential role of bile acids in bone metabolism among T2DM patients. The circulating TBA might be employed as an indicator of abnormal bone metabolism.